2010
DOI: 10.1148/radiol.10091224
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Perfusion in Nonmedicated Schizophrenic Patients: A Continuous Arterial Spin-labeling 3.0-T MR Study

Abstract: CASL in schizophrenia revealed patterns of hypo- and hyperperfusion similar to the perfusion patterns in previously published positron emission tomographic and single photon emission computed tomographic studies. The advantages of CASL, including independence from injected contrast agents, no irradiation, and fast acquisition time, may facilitate intensive perfusion studies of the early recognition of schizophrenia and other psychiatric disorders, as well as longitudinal disease-monitoring research of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 53 publications
10
63
0
2
Order By: Relevance
“…Overall, these studies reported seemingly mixed results, including increases (Friston, Liddle, Frith, Hirsch, & Frackowiak, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014; Talati, Rane, Skinner, Gore, & Heckers, 2015), decreases (Kindler et al, 2015; Nordahl et al, 1996; Scheef et al, 2010; Tamminga et al, 1992), or no differences (Horn et al, 2009; Ota et al, 2014; Vita et al, 1995). Beyond the hippocampus, other brain regions of significantly elevated resting perfusion in schizophrenia patients compared with healthy controls have involved the basal ganglia and middle temporal lobes (Pinkham et al, 2011), cerebellum, brainstem, and thalamus (Scheef et al, 2010). Noteworthy, while not directly focusing on the hippocampus as a specific region, initial PET and SPECT studies did not find increased perfusion in medial temporal regions (Andreasen et al, 1997; Catafau et al, 1994; Early, Reiman, Raichle, & Spitznagel, 1987; Parellada et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies reported seemingly mixed results, including increases (Friston, Liddle, Frith, Hirsch, & Frackowiak, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014; Talati, Rane, Skinner, Gore, & Heckers, 2015), decreases (Kindler et al, 2015; Nordahl et al, 1996; Scheef et al, 2010; Tamminga et al, 1992), or no differences (Horn et al, 2009; Ota et al, 2014; Vita et al, 1995). Beyond the hippocampus, other brain regions of significantly elevated resting perfusion in schizophrenia patients compared with healthy controls have involved the basal ganglia and middle temporal lobes (Pinkham et al, 2011), cerebellum, brainstem, and thalamus (Scheef et al, 2010). Noteworthy, while not directly focusing on the hippocampus as a specific region, initial PET and SPECT studies did not find increased perfusion in medial temporal regions (Andreasen et al, 1997; Catafau et al, 1994; Early, Reiman, Raichle, & Spitznagel, 1987; Parellada et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired parahippocampal recruitment during visual-memory encoding has been reported in patients and their siblings 37 . In our review, two small studies with the same sample size found divergent results in this region: while Scheef et al 14 (N = 11) described increased rCBF in this brain region, Walther et al 35 (N = 11) found precisely the opposite. Again, evidence is not enough to determine the rCBF patterns in the parahippocampus of patients with schizophrenia.…”
Section: Divergent Resultsmentioning
confidence: 58%
“…Of note, most of the divergent findings were described in the same study, by Scheef et al 14 (see Table 3 for details). putamen is in line with the results of studies using other neuroimaging methods and is probably a consequence of antipsychotic use 30 .…”
Section: Divergent Resultsmentioning
confidence: 76%
See 2 more Smart Citations